2022
DOI: 10.3389/fpls.2022.993194
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives of ubiquitination and SUMOylation in abiotic stress tolerance in plants

Abstract: Post-translational modification (PTM) is a critical and rapid mechanism to regulate all the major cellular processes through the modification of diverse protein substrates. Substrate-specific covalent attachment of ubiquitin and Small Ubiquitin-Like Modifier (SUMO) with the target proteins, known as ubiquitination and SUMOylation, respectively, are crucial PTMs that regulate almost every process in the cell by modulating the stability and fidelity of the proteins. Ubiquitination and SUMOylation play a very sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 187 publications
0
10
0
Order By: Relevance
“…Further potential PTMs of interest are mono‐ or multimonoubiquitinylation and SUMOylation. Both PTMs are important known regulatory signals for sorting, trafficking, and removal of diverse membrane proteins (Foot et al, 2017; Schwihla & Korbei, 2020; Singh et al, 2022). Notably, only recently first evidence for potential SUMOylation of ChR1 has been published (Sharma et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Further potential PTMs of interest are mono‐ or multimonoubiquitinylation and SUMOylation. Both PTMs are important known regulatory signals for sorting, trafficking, and removal of diverse membrane proteins (Foot et al, 2017; Schwihla & Korbei, 2020; Singh et al, 2022). Notably, only recently first evidence for potential SUMOylation of ChR1 has been published (Sharma et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…nIL‐33 is regulated by various post‐translational modifications, including SUMOylation, acetylation and ubiquitination. SUMOylation is a form of post‐translational modification in which small ubiquitin‐like modifier (SUMO) proteins are attached to target proteins (Singh et al 2022; Vertegaal 2022). Previous studies by the authors have suggested that nIL‐33 is subject to SUMOylation, with four potential sites for SUMOylation identified within the protein (Wang et al 2023b).…”
Section: Post‐translational Modifications and Functional Changes Of N...mentioning
confidence: 99%
“…However, there is limited available data on the ubiquitinome and sumoylome in the context of combined stress. Nevertheless, high temperature or drought-induced ubiquitination regulates ABA signalling ( Chiu et al., 2016 ; Yu et al., 2016 ; Xu and Xue, 2019 ), and ubiquitination regulates drought tolerance via the ABA signalling pathway ( Seo et al., 2012 ; Lim et al., 2017 ; Xu and Xue, 2019 ; Tong et al., 2021 ; Singh et al., 2022 ). High temperatures inhibit Arabidopsis seed germination by dampening both protein ubiquitination and proteasome activity in an ABA-dependent manner ( Chiu et al., 2016 ).…”
Section: Proteome Responses To Combined Heat and Droughtmentioning
confidence: 99%